(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
This work is aimed to develop polyethersulfone (PES) nanofiltration (NF) membrane with layer-by-layer (LBL) polyelectrolytes of chitosan (CHI) and poly(acrylic acid) (PAA) for xylitol purification from fermentation broth. Different number of bilayers and type of terminating layer were manipulated for producing more hydrophilicity, negatively charged with improved performance compared to pristine PES membrane. Successful deposition of polyelectrolyte layers onto PES membrane was able to be proven using various tests such as contact angle, Zetasizer and FT-IR. The results obtained have proven that LBL can develop PES membrane with higher resistance to fouling. From Zeta potential analysis, the value of pristine PES membrane’s negativity confirmed the theory of negatively charged substrate for LDL. The negative value of PES membrane increased from -16.5 mV to -32.7 mV after being modified to PES (CHI/PAA)6. From FT-IR spectra, the formation of CHI/PAA complexes on the membrane’s surface is confirmed through the presence of stretching peaks of -COOH, -NH3+ and -NH2+ groups The pure water flux reduces from 47.40 ±6.30 L⁄m2.h to 7.40 ±1.64 L⁄m2.h after being modified to PES (CHI/PAA)2. The rejection performance of xylitol for PES (CHI/PAA)2 is higher (84.95%) than pure PES membrane (66.17%), while (CHI/PAA)4 offered the lowest selectivity towards xylitol than arabinose and thus able to obtain higher purity of xylitol as retentate. LBL surface modification using CHI/PAA can develop PES membrane with higher hydrophilicity, negatively charge, and is able to give better xylitol rejection compared to pure PES.